2005
DOI: 10.1007/s10661-005-6023-5
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate leaching in agriculture to upper groundwater in the sandy regions of the Netherlands during the 1992–1995 period

Abstract: The Dutch National Monitoring Programme for Effectiveness of the Minerals Policy (LMM) was initiated to allow detection of a statutory reduction in nitrate leaching caused by a decreasing N load. The starting point, or baseline, was taken as the nitrate concentration of the upper metre of groundwater sampled on 99 farms in the 1992-1995 period in the sandy areas of the Netherlands, where predominantly grass and maize grow. We found here that a reduction in nitrate leaching of more than 20% in future would almo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 39 publications
1
23
0
3
Order By: Relevance
“…During sampling the groundwater level was recorded and in each sample DOC was measured. In addition, for each sample a value for the precipitation surplus was calculated (Boumans et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During sampling the groundwater level was recorded and in each sample DOC was measured. In addition, for each sample a value for the precipitation surplus was calculated (Boumans et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Especially N-surpluses are associated with losses from the system through nitrate leaching, ammonia volatilization and dissipation as N 2 or NO x Delgado 2002). The losses can negatively affect the quality of groundwater (Boumans et al 2005), surface water (Collingwood 1977;Jensen et al 1991) and air (Monteny 2000). Nitrate leaching to groundwater presents risks for drinking water supplies and is associated with eutrophication in streams and lakes (Hosper 1997;Scheffer 1998).…”
mentioning
confidence: 99%
“…However, downward movement of nitrate and dilution in the precipitation surplus determines to what extent the nitrate concentration in the upper groundwater is determined by the management of just 'year n -1'. ONZAT (Van Drecht 1983;OECD 1989) was used to calculate an index for dilution and duration of percolation for each measured nitrate concentration (Boumans et al 2005). Year-and locationspecific weather data from KNMI (the Royal Netherlands Meteorological Institute) were used as model input.…”
Section: Dilution and Duration Of Percolationmentioning
confidence: 99%
“…One approach to answer this question is to compare deciduous and coniferous forest stands under comparable local site conditions. Climate , soil type (Silva et al 2005;Boumans et al 2004), land use history (Matson et al 2002), pollutant emission level (Matson et al 2002), successional phase (Aber et al 1989;Å gren and Bosatta 1988;Cairns and Lajtha 2005), distance to forest edge (Weathers et al 2001), and experimental set-up (Bleeker et al 2003) are all known to have a significant impact on the element fluxes observed. The aim of this paper is to find out how coniferous and deciduous broadleaved forests differ in terms of element throughfall (+stemflow) deposition and seepage flux to groundwater.…”
mentioning
confidence: 99%